Local cultural values and language practices in shaping student learning behavior: a qualitative study in rural indonesia - Teti Berliani (Jurnal Konseling dan Pendidikan, 2026)
Previous studies on multilingual education in rural contexts have often overlooked how local cultural norms and language hierarchies jointly shape students’ learning engagement. This study addresses that gap by exploring the mechanisms through which local cultural values and linguistic practices influence student learning behavior in multilingual rural schools of Indonesia. Specifically, the study focuses on three behavioral dimensions: classroom participation, learning motivation, and comprehension strategies in culturally diverse learning settings. Employing a qualitative multiple case study design, data were collected from three rural schools across different provinces through semi-structured interviews with 24 participants (students, teachers, and parents), classroom observations, and short-term cultural immersion. Thematic analysis was conducted using NVivo software, supported by triangulation and member checking to ensure analytical validity. Findings reveal that learning behaviors are shaped by local cultural values, particularly respect for authority, collective identity, and language hierarchy, which mediate students’ participation and motivation. Students negotiate between home and school cultures, often resulting in passive engagement when formal teaching styles conflict with communal learning norms. Variations across sites highlight both shared cultural mechanisms and context-specific adaptations. The study concludes that culturally responsive pedagogy is essential for improving learning engagement in rural multilingual contexts. Practical implications include integrating cultural and linguistic competence into teacher education programs and aligning curriculum design with the sociolinguistic realities of rural Indonesia.